Cross-cultural adaptation and measurement properties of the Patient-Rated Tennis Elbow Evaluation for the Persian language. (June 2020) - Shafiee, Erfan; Farzad, Maryam; Macdermid, Joy; Smaeel Beygi, Amirreza; Vafaei, Atefeh; Farhoud, Amirreza
Introduction: The Patient-Rated Tennis Elbow Evaluation (PRTEE) questionnaire is a tool designed for self-assessment of forearm pain and disability in patients with tennis elbow. The aims of this study were to translate and cross-culturally adapt the PRTEE questionnaire into Persian and evaluate its reliability and construct validity. Methods: The PRTEE questionnaire was translated into and cross-culturally adapted to Persian in 90 consecutive patients with tennis elbow, according to well-established guidelines. Reliability was tested by means of test–retest and internal consistency. The measurement error was measured by calculating the standard error of measurement. Based on the standard error of measurement, the minimum detectable change was calculated. To evaluate construct and convergent validity, correlation with the PRTEE with the Disabilities of the Arm, Shoulder and Hand questionnaire and Visual analogue scale was used. Results: In the process of cross-cultural adaptation, two items (6 and 8) were modified. In item 6, the term "door knob" was changed to "turn a key", and in the item 8, "cup of coffee" was changed to "cup of milk". Item-total correlations were greater than 0.55 (ranged from 0.55 to 0.76), internal consistency was high (Cronbach's alpha, 0.94) and a high intraclass correlation coefficient (0.98) indicated excellent reliability of the P-PRTEE. The standard error of measurement and minimum detectable change were 5.40 and 14.24, respectively. The Persian version of the PRTEE questionnaire (P-PRTEE) shows strong construct and convergent validity ( r values = 0.85, p < 0.05). Conclusions: The P-PRTEE is valid and reliable in assessing disability and pain in Persian patients with tennis elbow. The excellent psychometric properties of the P-PRTEE endorse the use of this questionnaire in clinical settings.